Um sistema para classificação e análise de qualidade de sanidade de cruzetas de madeiras - Silva, Carlos Alberto Lopes da (2016)
Deterioration problems in woods are constant and involve many studies to determine the useful life of the same in buildings, poles, fences, sleepers, etc. In this work, a technique is developed to determine the useful life of wood used in crosspieces to support electrical cables. The useful life of poles of wood is defined as health status. In the studies are considered three health states where, for each state, different data collections were made. The data were classified with the signal capture through use of specific microphone, extraction of FFT, LPC, MFCC, ENERGY, ZERO CROSSING and AREA coefficients to determine the characteristics of these signals. The K-NN algorithm is used for training the characteristics of each state of health. At the end it was generated specific equipment for the field testing of sanities proposals.